Potentiella virala zoonoser hos apor på svenska djurparker år 2008 - Skierus, Joakim (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2010)
This paper is a compilation of some of the important viral zoonosis that can be passed from apes and simians (simian and prosimian) to man. Viral zoonoses are viral diseases that can be passed from animals to humans. The paper will also provide a better insight of the risks workers and visitors to the zoo can be exposed to. The viruses that this paper is focused on is herpes Bvirus, simian T-lymphotropic virus type 1 (STLV), simian immunodeficiency virus (SIV), Ebola virus, Marburg virus, yellowfever virus, monkeypoxvirus and hepatitis B virus. The choice of viruses is based on how infectious they are and how pathogenic they are. There are several associations in the world related to health, trade and management of zoo animals that have developed guidelines for which viruses to test for in different monkeys.